Decision-making model of sustainable ecological environment management based on enterprise environmental management under a low-carbon economy - Li, Xiaoao; Gao, Jiangang (Frontiers in Energy Research, 2023)
With the development of industrialization, ecological and environmental problems have become increasingly prominent. In addition, the direct burning of crop straw and livestock manure also causes serious damage to the ecological environment. From the perspective of low-carbon economy, in order to promote the sustainable development of the ecological environment, this paper puts forward the idea of integrating the environmental management of enterprises, establishes the decision-making model of ecological environment management, and carries out related research. The experimental results show that the average error of cross-section water quality prediction is 2, the average error of pollutant discharge prediction is 2.1, and the highest ecological security degree is 1.28. The data show that the system dynamics method can effectively reduce the section water quality prediction error and pollutant discharge prediction error of the management decision-making model, and improve the accuracy of the model prediction. In the analysis experiment of the biomass energy potential of agricultural waste, livestock manure and straw waste accounted for 59.26% and 30.18% of the total, respectively. It can be seen that agricultural waste has a high content of convertible biomass energy, which can provide a large amount of renewable energy for human beings.